Pronunciation of double consonants at the border of a prefixes, or, A prefix and a root in the Russian language : (on the material of orthoepic dictionaries published by the Russian Academy of Sciences) - Jelena Ginić (Opera slavica, 2025)
In this paper, on the material extracted from orthoepic dictionaries of different generations, we observe the development of the pronunciation of doubled consonants at the border of prefixes or prefixe and root. A large number of examples (about 44.5 %) have no changes in pronunciation: the long voice was pronounced in all generations of orthoepic dictionaries. Changes exist in about 55.5 % of the examples and are reflected in the fact that in the younger generation of dictionaries, a variant pronunciation is possible in the case when only a long consonant was recorded in the middle and older generation (about 16.5 %), that in the examples in which had pronunciation variants in the middle and older generations of the dictionary, in the younger ones there are multimember orthoepemes (about 16.5 %), that in all generations the long voice is pronounced, with the fact that in the middle and older generations it is a long soft voice, while in to the younger generation, it is the voice with a hard beginning, a soft ending (11.1 %), the long voice in the older and middle generation of the dictionaries was replaced by a simple voice in the younger generation (8.3 %), and finally, a simple voice in the younger and middle generation, while in the older generation the pronunciation of the simple voice was only permitted, in addition to the more normative pronunciation of the long voice (3.6 %). We also came to the following conclusions: hard voices carry a greater potential for long pronunciation than soft voices; dictionaries give hard explosive consonants a greater potential for the realization of a doubled voice when dealing with an intervocalic position than hard fricative voice; the distance between the place of the doubled voice and the place of the accent increases the potential for the appearance of a variant pronunciation (the pronunciation of the simple voice is also recorded). In the younger generation of dictionaries, long sounds with different softness (beginning hard, ending soft) are realized, which were not found in earlier generations of dictionaries.